2018
DOI: 10.1186/s12877-017-0700-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled intervention study investigating the efficacy of carotenoid-rich fruits and vegetables and extra-virgin olive oil on attenuating sarcopenic symptomology in overweight and obese older adults during energy intake restriction: protocol paper

Abstract: BackgroundWeight loss interventions have not been advocated for overweight/obese older adults due to potential loss of skeletal muscle and strength impacting on physical function with potential loss of independence. Carotenoids and polyphenols are inversely associated with sarcopenic symptomology. This paper reports the protocol of a study evaluating the efficacy of a high-protein, energy restricted diet rich in carotenoids and polyphenols on body composition, muscle strength, physical performance and quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 79 publications
1
18
0
1
Order By: Relevance
“…The effect of OLE attenuating body weight loss in old rats may be explained, at least in part, by the significant increase in muscle mass in old treated rats since skeletal muscle accounts for approximately 40% of total body mass. In agreement with this, it is reported that supplementation with secoiridoids from olive oil attenuates sarcopenia in overweight and obese older adults 30 .…”
Section: Discussionsupporting
confidence: 74%
“…The effect of OLE attenuating body weight loss in old rats may be explained, at least in part, by the significant increase in muscle mass in old treated rats since skeletal muscle accounts for approximately 40% of total body mass. In agreement with this, it is reported that supplementation with secoiridoids from olive oil attenuates sarcopenia in overweight and obese older adults 30 .…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, a recent study showed that higher dietary intake of antioxidants including vitamin E, and vitamin C (especially, vitamin C) and carotenoid were reversely associated with indices of sarcopenia in women [175]. Consistency, carotenoid-and polyphenol-rich diet ameliorated the skeletal muscle atrophy [176]. However, the use of the antioxidant supplement for sarcopenia patients need to be further explored.…”
Section: Molecular Strategies To Develop Therapeutics For Sarcopeniamentioning
confidence: 99%
“…One of the most important lifestyle factors is the diet. Epidemiological studies have shown that diets with consumption patterns rich in fruits and vegetables could have an impact on glucose levels in diabetic patients (Mellendick et al, 2018;Ramírez-Silva et al, 2009;Villani et al, 2018). Polyphenols are one of the most abundant group of bioactive compounds in plants, fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%